Modelos de ìndices de sitio para Ochroma Pyramidale (balsa) en el Litoral Ecuatoriano, año 2015 - Vite Jiménez, Kleber Javier (2016)
This research was made in the Ecuadorian coastal region, in 20 counties (Eloy Alfaro, Esmeraldas, Quinínde, San Lorenzo, El Empalme, Naranjal, Babahoyo, Buena Fe, Mocache, Montalvo, Quevedo, Quinsaloma, Valencia, Chone, Junín, Pichincha, Portoviejo, Manga del cura, La Concordia y Santo Domingo) in five provinces, from a database of 2069 sampling units plantations Ochroma pyramidale (basa). circular plots of 12,62 m radius (500 m2) were used. In each plot the total height of 50 trees was measured raft. three asymptotic models were applied to all field data in relation to the maximum / age stands of balsa height were evaluated. The statistical model was based on the interpolation method Kriging is an advanced geostatistical procedure that generates an estimated from a set of points with z values scattered surface. The results showed that the best fit of selected models with different tentative values b was obtained as the best model Chapman-Richard with a value of 0,0865, being Hossfeld a b of 1,4986 and with a value of Levakovic b of 1,9683. For predicting Site Index for balsa model Chapman-Richard in this research has a better comportmiento adjustments in its benefits, with a value of coefficient of determination (r2) of 0,84, Chapman model Richards showed distortion values of 1,2 % and also for accuracy 9,8 %. 1 site quality excellent for the raft is in the cantons of Eloy Alfaro, Quininde, San Lorenzo, El Empalme, Buena Fe, Mocache, Quevedo, Valencia, Chone, Pichincha, Manga priest, the Concordia and Santo Domingo. The quality of room 2 good for the raft is in the cantons of Esmeraldas, Quinsaloma and Junin. Site quality 3 fair for the raft is located in the city of Portoviejo and site quality 4 bad for the raft is in the cantons of Naranjal, Babahoyo and Montalvo.